Etika Lingkungan dalam Islam: Kajian Hadis tentang Larangan Membunuh Serangga - Hasanah, Dina; Sulidar, Sulidar (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
This study aims to explore the concept of environmental ethics in Islam, focusing on the study of hadiths that discuss the prohibition or regulations regarding killing insects. The main objective of the research is to understand Islamic ethical values related to the protection of small living creatures as part of the environment, as well as their implications for human behavior in maintaining ecological balance. The research method used is a library study with a qualitative approach. Data were collected from primary sources, namely hadiths of Prophet Muhammad (peace be upon him) concerning the killing of insects and small living beings, as well as secondary sources including fiqh literature, tafsir, and books on environmental ethics in Islam. The analysis was conducted using descriptive critical techniques to interpret the meaning of the hadiths and their relevance in the context of modern environmental ethics. The results indicate that Islam upholds principles of maintaining the balance of nature and the rights of all living creatures, including insects. The hadiths that regulate the prohibition of killing insects without valid reasons emphasize the values of tolerance and respect for all creatures created by Allah. The Islamic concept of environmental ethics encourages environmentally friendly attitudes and the preservation of living beings as part of the human responsibility on earth. In conclusion, environmental ethics in Islam teaches the importance of protecting all living beings regardless of their size, including insects. This hadith-based study provides a strong moral foundation for fostering ecological awareness and human responsibility in conserving the environment.